Recent patents related to phosphorylation signaling pathway on cancer - Acosta, Karina Beatriz (2011)
Phosphorylation and dephosphorylation play an important role in the regulation of growth factor and cytokine signal transduction to modulate cell proliferation, differentiation, survival, and apoptosis. In some cellular systems, the information suggests that EGFR, somatostatin receptors, SHP-1, Akt and PI3K can regulate carcinogenesis implied process through regulated the activity of NF-κB. Current patents related to signaling pathway that includes somatostatin receptors, phosphotyrosine phosphatases, tyrosine kinases, AKT/PKB and PI3K are focusing in diagnosis, prognosis and treatment. Many recent patented techniques include inhibition, antagonism or alternative therapeutic methods. Furthermore, it is necessary to deepen understanding of the molecular mechanisms involved in cancer to develop other alternative therapies focusing not only on new inhibitors. © 2011 Bentham Science Publishers.